2013
DOI: 10.3329/bjvm.v10i1-2.15648
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diseases of Ruminants Recorded at the Patuakhali Science and Technology University Veterinary Clinic

Abstract: This study was conducted at the Patuakhali Science and Technology University Veterinary Clinic, Babugonj, Barisal during the period from January 2008 to December 2011 to report the four years clinical diseases of ruminants. A total of 1241 clinical cases (793 cattle and 448 goats) were recorded and analyzed. Diagnosis of each of the clinical cases was made on clinical history, clinical signs, and faecal examination for parasitic cases. The clinical cases were primarily categorized into three major groups, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
57
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(98 citation statements)
references
References 3 publications
26
57
15
Order By: Relevance
“…Analysis of the clinical cases of ruminants revealed that 5% cattle and 4.44% goats were affected with fever of unknown etiology. Samad and Rahman (Samad et al, 2002;Rahman et al, 2012) reported that the of 5.1% to 12.1% occurrence of fever in this study supports the earlier reports of cases of fever in cattle and 10.37% and 4.4% fever cases in goats (Rahman et al, 2012). Anorexia: Anorexia was reported in 8.33% cattle and 4.44% in goats.…”
Section: Diseases and Disorders Of Cattle And Goatsupporting
confidence: 80%
See 4 more Smart Citations
“…Analysis of the clinical cases of ruminants revealed that 5% cattle and 4.44% goats were affected with fever of unknown etiology. Samad and Rahman (Samad et al, 2002;Rahman et al, 2012) reported that the of 5.1% to 12.1% occurrence of fever in this study supports the earlier reports of cases of fever in cattle and 10.37% and 4.4% fever cases in goats (Rahman et al, 2012). Anorexia: Anorexia was reported in 8.33% cattle and 4.44% in goats.…”
Section: Diseases and Disorders Of Cattle And Goatsupporting
confidence: 80%
“…Diarrhoea cases were 6.66% in cattle and 6.66% in goats. These observations could be compared well with the 6.94% of non-specific diarrhoea in dairy cows, 8.99% in cow-calves and 12.23% in goats Samad, 1996, 1997) and 7.6% in cattle and 12.1% in goats (Rahman et al, 2012). Samad (2001) reported 25.97% and 9.91% of diarrhoeal diseases in cattle and goats, respectively.…”
Section: Diseases and Disorders Of Cattle And Goatsupporting
confidence: 61%
See 3 more Smart Citations